Electromagnetic Fields and Human Endocrine System - Michal Karasek; Marta Woldanska-Okonska (The Scientific World Journal)
Extremely low frequency electromagnetic fields (ELF EMF) are commonly present in daily life all over the world. Moreover, EMF are used in the physiotherapy of many diseases because of their beneficial effects. There is widespread public concern that EMF may have potential consequences for human health. Although experimental animal studies indicate that EMF may influence secretion of some hormones, the data on the effects of EMF on human endocrine system are scarce. Most of the results concentrate on influence of EMF on secretion of melatonin. In this review, the data on the influence of EMF on human endocrine system are briefly presented and discussed.